Le monde des lecteurs de Spore(1.7) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Vous devriez traiter davantage de l'agriculture urbaine et de son expansion. -Jac Smit, The Urban Agriculture Network